Determination of the optimal soil sample size to accurately characterise nematode communities in soil. (January 2015) - Wiesel, Lea; Daniell, Tim J.; King, Dale; Neilson, Roy
Abstract: Analysis of nematode communities is a potential biological proxy to monitor soil health. Traditionally, nematodes are extracted from 200 g of soil and then identified based on morphology. However, the optimal soil sample size to accurately characterise nematode communities using molecular methods is unknown. Using a combined relative real-time PCR and T-RFLP approach we analysed nematode communities extracted from triplicate samples ranging from 1 to 200 g soil. Our data indicated that for molecular based analyses, soil sample sizes <200 g of soil do not accurately represent the abundance of nematodes and <100 g samples are less likely to reflect the true community composition. Thus characterisation of nematode communities from low sample sizes may not be robust. Highlights: Relative real-time PCR is a good measure of nematode abundance at 200 g sample size. Nematode community composition differed between low and high weight soil samples. Soil samples of >100 g are needed to truly represent nematode community composition.